Roussel Uclaf Causality Assessment Method for Drug-Induced Liver Injury: Present and Future - Danan, Gaby; Teschke, Rolf (Frontiers in Pharmacology, 2019)
Among causality assessment methods used for the diagnosis of drug-induced liver injury (DILI) Roussel Uclaf Causality Assessment Method (RUCAM) remains the most widely used not only for individual cases but also for prospective and retrospective studies worldwide. This first place is justified by the characteristics of the method such as precise definition and classification of the liver injury which determines the right scale in the scoring system, precise definition of the seven criteria and the validation approach based on cases with positive rechallenge. RUCAM is used not only for any types of drugs but also for herbal medicines (HILI) and dietary supplements. In 2016 the updated RUCAM provided further criteria and instructions to improve inter observer variability. Although this method was criticized for criteria such as the age and alcohol consumption, recent consensus meeting of experts has recognized their value and recommend their incorporation into any method. While early studies searching for DILI in large databases especially in electronic medical records were based of codes of diseases or natural language without causality assessment, the recommendation is now to include RUCAM in the search for DILI/HILI. There are still studies on DILI detection or the identification of biomarkers that take into consideration the cases assessed as “possible” although it is well known that these cases reduce the strength of the association between the cases and the offending compound or the new biomarker to be validated. Attempts to build electronic RUCAM or automatized application of this method were successful despite some weaknesses to be corrected. In the future more reflexions are needed on an expert system to standardize the exclusion of alternative causes according to the clinical context. Education and training on RUCAM should be encouraged to improve the results of the studies and the day to day work in pharmacovigilance departments in companies or in regulatory agencies. It is also expected to improve RUCAM with biomarkers or other criteria provided that the validation process replaces expert opinion by robust standards such as those used for the original method.